Visual Power in Ancient Greece and Rome : Between Art and Social Reality - Hölscher, Tonio (Sather Classical Lectures, 2018)
Cover -- VISUAL POWER IN ANCIENT GREECE AND ROME -- Title -- Copyright -- CONTENTS -- List of Illustrations -- Periods of Greek and Roman History -- Acknowledgments -- Introduction. Visuality and Viewing in Ancient Greece and Rome -- 1. Space, Action, and Images -- 2. Time, Memory, and Images -- 3. Person, Identity, and Images -- 4. The Dignity of Reality -- 5. Representation -- 6. Decor -- Notes -- General Index -- Index of Names -- Index of Sites and Museums.